2023
DOI: 10.20517/mrr.2023.59
|View full text |Cite
|
Sign up to set email alerts
|

Folate-producing bifidobacteria: metabolism, genetics, and relevance

Maria Rosaria D’Aimmo,
Maria Satti,
Donatella Scarafile
et al.

Abstract: Folate (the general term for all bioactive forms of vitamin B9) plays a crucial role in the evolutionary highly conserved one-carbon (1C) metabolism, a network including central reactions such as DNA and protein synthesis and methylation of macromolecules. Folate delivers 1C units, such as methyl and formyl, between reactants. Plants, algae, fungi, and many bacteria can naturally produce folate, whereas animals, including humans, must obtain folate from external sources. For humans, folate deficiency is, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 107 publications
(242 reference statements)
0
4
0
Order By: Relevance
“…For instance, some particular strains of LAB or Bifidobacteria have the ability to produce vitamins such as the folate-producing probiotic strains Bifidobacterium longum B6 and ATCC 15,708, Lactobacillus acidophilus N1 and ATCC 4356, Lactobacillus delbrueckii ssp. bulgaricus 448 and 449, and Streptococcus thermophilus MC and 573 [ 60 ], Lactobacillus sakei strains CRL 2209 and CRL 2210 [ 61 ] and Bifidobacterium catenulatum ATCC 27,539 [ 62 ]. Also, a study evaluating the in vitro potential of four probiotic bacterial strains to produce and release de novo SCFAs and selected B-vitamins found that B. longum SP 07/3 and B. bifidum MF 20/5 were able to synthetize in vitro thiamine but unable to synthesize folates or riboflavin [ 52 ].…”
Section: Vitamins and Minerals As Key Actors In Host Energy Metabolis...mentioning
confidence: 99%
“…For instance, some particular strains of LAB or Bifidobacteria have the ability to produce vitamins such as the folate-producing probiotic strains Bifidobacterium longum B6 and ATCC 15,708, Lactobacillus acidophilus N1 and ATCC 4356, Lactobacillus delbrueckii ssp. bulgaricus 448 and 449, and Streptococcus thermophilus MC and 573 [ 60 ], Lactobacillus sakei strains CRL 2209 and CRL 2210 [ 61 ] and Bifidobacterium catenulatum ATCC 27,539 [ 62 ]. Also, a study evaluating the in vitro potential of four probiotic bacterial strains to produce and release de novo SCFAs and selected B-vitamins found that B. longum SP 07/3 and B. bifidum MF 20/5 were able to synthetize in vitro thiamine but unable to synthesize folates or riboflavin [ 52 ].…”
Section: Vitamins and Minerals As Key Actors In Host Energy Metabolis...mentioning
confidence: 99%
“…Cells that rapidly divide, such as blood and gut cells, especially need high folate levels to support their rapid growth [136]. Humans and other animals cannot synthesize folate naturally; it must be obtained through diet (like leafy greens, yeast, liver, and beans) or through beneficial gut bacteria capable of producing folate [138][139][140]. Inadequate folate levels are connected to numerous health issues, including neural tube defects during embryonic development, anemia, cancer risk, and cardiovascular illnesses [141][142][143].…”
Section: Folate Productionmentioning
confidence: 99%
“…Bifidobacteria are known for synthesizing a range of B vitamins, such as folate, biotin, thiamine, nicotinic acid, pyridoxine, riboflavin, and vitamin B12, although they have not been shown to produce vitamin K [140,144]. The study of bifidobacteria's ability to both synthesize vitamins and release them outside the cell is still not thoroughly examined, with folate being the exception.…”
Section: Folate Productionmentioning
confidence: 99%
“…The lactose from milk is degraded to acid during the fermentation process, which causes pH reduction. Kefir is a good source of Mg, Ca, and P, and, in addition to vitamins in the milk, many vitamins can also be synthesized by LAB during fermentation such as B1, B2, B5, C, and B12 [ 29 ]. Finally, several compounds that are generated during fermentation exert a direct influence on the aroma and taste of kefir, such as lactic, acetic, pyruvic, hippuric, propionic, and butyric acids, diacetyl, and acetaldehyde [ 30 ].…”
Section: Introductionmentioning
confidence: 99%